Exploration of the Spanish Version of the Attachment Style Questionnaire: A Comparative Study between Spanish, Italian, and Japanese Culture - Oscar López-; Mᵃ Alejandra Koeneke Hoenicka; José Luis Martinez-Rubio; Kazuyuki Shinohara; Gianluca Esposito; Giuseppe Iandolo (MDPI AG, 2021)
Nowadays, there are several human attachment measures, most in the form of questionnaires that assess adult attachment styles. This study investigates the use of Feeney, Noller, Hanrahan, Sperling and Berman's five-factors Attachment Style Questionnaire (ASQ, 1994), based on Bartholomew's four-factors model (1991), and Hazan and Shaver's three-factors model (1987). Nevertheless, no robust study has explored the ASQ questionnaire in Spanish compared to other cultures, such as Italian and Japanese. Therefore, the linguistic translation of the Spanish version of the ASQ was performed, based on the back-translation methodology. The results indicate that 5-factors ASQ Spanish version explains 43.67% of the variance, similar to the original English-Australian ASQ version. The Italian and Japanese versions explain 49.37% and 52.27% of the variance, respectively. No age correlation for any ASQ factors in the Japanese sample was found; meanwhile, the Spanish and Italian cultures showed a positive correlation with age and "Confidence" and negative correlation with age and "Relationships as Secondary" ASQ factors. Some transcultural differences and possible research approaches are addressed.